Fanuel Community, media mediation and folkreligious activism in Parintins/Am (Revista Internacional de Folkcomunicação, 2024)
This article analyzes the constitution of the folkreligious leader of the Fanuel Catholic Community, in Parintins/Am, and his performance as a media activist on the community's Facebook page. Qualitative research that adopts the ethnographic and netgraphic model for a description and interpretation of the characteristics of a folkmedia communicator. The study is articulated with Luiz Beltrão's folkcommunicational theory; it also dialogues with Recuero (2014) and Scherer; Farias (2018) on the basic aspects that promote communication on Facebook; with the notions of field, in Pierre Bourdieu. Amid the interest of the mainstream media in folklore manifestations, the concept of media activist by Trigueiro (2013) emerges. To glimpse the practices of these leaders on Facebook is to perceive them as folk-religious activists who have appropriated the tools and techniques of the Facebook social network to transmit the charisma of the community in question.